PEMASANGAN PIPA GAS BAKAR MENARA OBOR DI LEPAS PANTAI DENGAN ALAT ANGKAT NON CRANE - Sulardi Sulardi; Lukman Lukman; Basyaruddin Basyaruddin (Sekolah Tinggi Teknologi MIGAS, 2022)
The aim of the study is to provide an overview of the installation of a torch tower fuel gas distribution pipe offshore non using crane. The problem faced in the implementation of the installation is the difficulty of installing the fuel gas distribution pipe because there is no conventional crane lifting equipment that can be used at a height of 175 meters, weighing 115 tons and in very limited work locations. The solution to overcome the problem is to divide the gas distribution pipe into several trunks and install it on the derick structure by lifting the pulley system (non crane). The results showed that the lifting method using a pulley was proven to be suitable and safe to use for installing a gas pipeline for torch towers offshore. The results of this study also recommend that work methods can be replicated by other work units that experience similar problems.